Secured energy optimized Ad hoc on-demand distance vector routing protocol. (November 2018) - Amutha, S; Balasubramanian, Kannan
Abstract: A Mobile Ad hoc network (MANET) forms a group of mobile nodes which are active and exchange messages using interconnections between the nodes. The mobile network is the new generation of wireless network and differs from the wired network in the use of power-aware routing protocols, ease of routing configuration and network infrastructure. The proposed work identifies and resolves the black hole attack and provides security to the routing protocol by using a secured energy-optimized expanding ring search (ERS) algorithm. Also, this technique reduces the energy consumption and improves the network lifetime. In addition, this work focuses on improving the packet delivery ratio (PDR), throughput and security using the advanced encryption standard (AES) cryptographic algorithm.